(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was conducted on 100, day old guinea fowls (Pearl variety) for 12 weeks to study the efficacy of fenugreek (Trigonella foenum-graecum) and kalonji (Nigella sativa) seed powder supplementation on carcass traits and meat composition of thigh and breast. The experimental guinea fowls were randomly divided into five treatment groups viz. T1 control, T2 (2.0% fenugreek seed powder), T3 (1.0% kalonji seed powder), T4 (2.0% fenugreek +1.0% kalonji seed powder) and T5 (1.0% fenugreek + 0.5% kalonji seed powder), with two replications of ten guinea fowls each. The supplementation was done for 84 days. On 84th day, three guinea fowls from each replicate (6 guinea fowls/treatment) were sacrificed for study of carcass yield, cut up parts, organ weights and processing losses. The results indicated that dietary fenugreek and kalonji seed powder supplementation in guinea fowls improved dressed yield in T4 group of guinea fowls. Cut up parts in terms of thigh weights were improved in fenugreek and kalonji seed powder supplemented groups with maximum weight observed in T5 group of guinea fowls whereas breast weight was significantly increased in T4 group of guinea fowls. From the results of present study, it can be concluded that combination of fenugreek (2%) and kalonji (1%) seed powder through feed may be advised to improve carcass yield in guinea fowls.